Correction to: Persistent poor glycaemic control in individuals with type 2 diabetes in developing countries: 12 years of real-world evidence of the International Diabetes Management Practices Study (IDMPS) - Aschner, Pablo (2020)
Unfortunately, the standard deviations for ‘last HbA1c measurement’ in mmol/mol were miscalculated in Table 1 of this paper. Erratum for: Persistent poor glycaemic control in individuals with type 2 diabetes in developing countries: 12 years of real-world evidence of the International Diabetes Management Practices Study (IDMPS). Aschner P, Gagliardino JJ, Ilkova H, Lavalle F, Ramachandran A, Mbanya JC, Shestakova M, Chantelot JM, Chan JCN. Diabetologia. 2020 Apr;63(4):711-721. doi: 10.1007/s00125-019-05078-3.